A Festa do Peixe como Patrimônio do Povo Aikewara, São Geraldo do Araguaia no Estado do Pará - Teixeira, Thomas Rafael Alves (2019)
The study aimed to understand the meaning of party fish for the Suruí Aikewara, in the Village Sororó, in the state of Pará. To this end it was made a description of this ritual and then found to tackle the question of patrimony in the conflict that permeates these relations. We conducted a field survey, with data collected from interviews with students the Surui Aikewara of the class travel of Indigenous Intercultural Degree. Considerables informations was obtained that enables us to understand the importance of this ritual has to Aikewara and what idea they have of patrimony. Conflicts are perennials, because are in the village everyday, so to analyze them is used categories such as resignification of Garcia Canclini (2008), social process of Turner (1975) and cultural heritage proposed by Gallois (2011). It was found that the party Fish, like other rituals, plays an important role in the intergenerational transmission of Aikewara culture, where the older people play a key role of the transfer of knowledge necessary for their realization